EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING, TEAM ASSISTED INDIVIDUALIZATION DAN STUDENT TEAMS ACHIVEMENT DIVISIONS DENGAN PENDEKATAN SAINTIFIK TERHADAP PEMAHAMAN KONSEP DAN KETRAMPILAN KOMPUTASI MATEMATIKA DITINJAU DARI ADVERSITY QUOTIENT - Ardiyanto, David; Budiyono, Budiyono; Usodo, Budi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of this research was to know the effect of the Problem Based Learning (PBL), Teams Assisted Individualization (TAI), and Students Teams Achievement Divisions (STAD) with the scientific approachÂ viewed from students Adversity Quotient (AQ). The results of the research were as follows. (1) Students who were subjected to the PBL have a better understanding of concepts than students with the TAI while students were subjected to TAI have the same understanding of concepts as students who with STAD (2) Students who were subjected to the PBL have the same computing skills as students with the TAI, and TAI have the same computing skills as students with STAD, but students who were subjected to the PBL have better computing skills than students with STAD. (3) Students with high AQ have better conceptual understanding than students with medium and low AQ, and the students with medium AQ were better than low AQ. (4) Students with high AQ has better computing skills than students with medium and low AQ, and students with medium AQ have the same computing skills as low AQ. (5) In each of the learning model, students with high AQ have a better understanding of concepts than students with medium and low AQ, and students with medium AQ have a better understanding of concepts than low AQ. (6) In each of the learning model, students who have high AQ have better computing skills than students who have medium and low AQ, and students with medium AQ have the same computing skills equally as students who have low AQ. (7) In each AQ, students were subjected to the PBL have better understanding of concepts than students who were subjected to the TAI while students who were subjected to TAI have the same understanding of concept as with students who were subjected to the STAD. (8) In each AQ, students with the PBL have the same computing skills as students with TAI, students with TAI have the same computation skills as students ofÂ STAD, but students who were subjected to the PBL has the computing skills has better than students with STAD.Keywords : Learning model of PBL, TAI, STAD, scientific approach, Adversity Quotient (AQ), conceptual understanding, computation skill.